Bahasa ingris - Darni Sukma; T Alamsyah (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2023)
HIV (Human Immunodeficiency Virus) is a virus that weakens the immune system. Meanwhile, AIDS (Acquired Immune Deficiency Syndrome) means a collection of disease symptoms resulting from a decline in the body's immune system which is acquired, not congenital. The aim of this research is to determine the knowledge and attitudes of teenagers regarding HIV/AIDS towards students at SMA Negeri 2 Kuala, Nagan Raya Regency. This research method uses quantitative research methods with a cross-sectional approach design. The population in this study were 50 students from SMA Negeri 2 Kuala, Nagan Raya Regency. The sampling technique used a saturated random sampling technique to determine the sample because the sample only consisted of 50 people. The results of the study showed that the variable knowledge of high school students about HIV/AIDs was positively related to students at SMA Negeri 2 Kuala, Nagan Raya Regency. The attitude variable of high school students regarding HIV/AIDs is positively related to students at SMA Negeri 2 Kuala, Nagan Raya Regency. The conclusion of the research results shows that respondents have good knowledge and positive attitudes towards teenagers about HIV/AIDS. It is hoped that educational institutions can maintain youth knowledge and attitudes and improve them by holding guidance and counseling programs, especially regarding HIV/AIDS